Effects of the Pinggan Qianyang Recipe on MicroRNA Gene Expression in the Aortic Tissue of Spontaneously Hypertensive Rats. (25th August 2015) - Zhong, Guangwei; Fang, Xia; Wang, Dongsheng; Chen, Qiong; Tang, Tao
Abstract : The present study aimed to investigate the relationship between miRNAs and in spontaneously hypertensive rats (SHR) vascular remodeling and analyze the impact of the Pinggan Qianyang recipe (PQR) on miRNAs. Mammalian miRNA microarrays containing 509 miRNA genes were employed to analyze the differentially expressed miRNAs in the three groups. MiRNAs were considered to be up- or downregulated when the fluorescent intensity ratio between the two groups was over 4-fold. Validation of those miRNAs changed in SHR after PQR treatment was used by real-time quantitative RT-PCR (qRT-PCR). Compared with the normal group, a total of 32 miRNAs were differentially expressed by more than twofold; among these, 18 were upregulated and 14 were downregulated in the model group. Compared with the normal group, there were a number of 17 miRNAs which were significantly expressed by more than twofold in the different expressions of 32 miRNAs; among these, 10 were downregulated and 7 were upregulated in the PQR group. qRT-PCR verified that miR-20a, miR-145, miR-30, and miR-98 were significantly expressed in the three groups. These data show that PQR could exert its antihypertensive effect through deterioration of the vascular remodeling process. The mechanism might be associated with regulating differentially expressed miRNAs in aorta tissue.